Experimental study on atmospheric pressure plasma polymerized conducting polymer under coupling and remote conditions. (4th March 2018) - Kim, Dong Ha; Park, Choon-Sang; Jung, Eun Young; Kum, Dae Sub; Kim, Jae Young; Kim, Daseulbi; Bae, Gyu Tae; Cho, Byung-Gwon; Shin, Bhum Jae; Lee, Dong Ho; Chien, Sung-Il; Tae, Heung-Sik
ABSTRACT: This article has analyzed conducting polymer from the viewpoint of material properties, which is polymerized under atmospheric pressure condition for coupling and remote conditions, respectively. The experimental results show that the atmospheric pressure plasma polymerized pyrrole (pPPy) exhibits similar characteristics from the viewpoint of crystallinity, but the shapes and roughness of the particles are significantly distinguished. In the case of coupling condition, a uniform and flat layer like a thin film was obtained. However, in the case of remote condition, the deposited layer had more rough nanoparticles compared to that of coupling condition. The pPPy surface characteristic and morphology changes are discussed by using field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM), and X-ray diffraction (XRD) results. Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) analysis are used to determine the chemical changes introduced by the atmospheric pressure plasma for coupling and remote conditions. The both pPPy materials, which were obtained by coupling and remote conditions, are expected to be applied to various fields, especially for designing the thin conducting electrode layer of polymer light emitting diode (P-LED) or for improving the efficiency by inserting conducting polymer powder on hole injection layer.